Ex vivo human placental transfer study on recombinant Von Willebrand factor (rVWF). (August 2021) - Pastuschek, J.; Bär, C.; Göhner, C.; Budde, U.; Leidenmuehler, P.; Groten, T.; Schleußner, E.; Markert, U.R.
Abstract: Deficiency or mutation of von Willebrand factor (VWF) leads to a coagulation disorder (von Willebrand disease; VWD) which requires a lifelong therapy. For avoiding maternal complications treatment may be necessary also in pregnancy, but placental transfer to the fetus might impact its coagulation system and evoke undesired side effects. As VWF is a very large molecule it may be assumed that it does not pass the placental barrier. To prove this hypothesis the materno-fetal transfer of recombinant VWF (rVWF) has been analyzed ex vivo in a total of 21 valid dual side placenta perfusions. Three groups of five placentas each have been perfused with physiological and up to ten-fold increased concentrations of rVWF for 2 h. Six placentas have been used for control perfusions. A series of different control parameters has been assessed for documentation of intactness and functionality of the placenta and the perfusion system. In not a single analysis, independent of time and concentration, rVWF was detected in the fetal circuit. In the maternal circuit VWF concentration decreased slightly during perfusion. These results demonstrate that recombinant VWF does not pass the human placenta. Highlights: Recombinant von Willebrand factor (VWF) does not cross human placenta in 2 h ex vivo perfusion. No major placenta function is affected upon exposure to VWF. Control parameters have shown intactness of placenta barrier and perfusion system.